2020
DOI: 10.5194/tc-2020-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permafrost thawing exhibits a greater influence on bacterial richness and community structure than permafrost age in Arctic permafrost soils

Abstract: Abstract. Global warming accelerates permafrost thawing and changes permafrost microbial community structure, but little is known about how microorganisms in permafrost with different ages respond to thawing. Herein, we disentangled the relative importance of permafrost age (young, medium, old, and ancient) spanning from 50 to 5,000 yr and thawing status (active, transitional, and permanently frozen) in shaping bacterial community structure using Hiseq sequencing of the 16S rRNA gene. Our results revealed sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In our study, the bacterial community diversity varied significantly between the active layer and permafrost layer. Studies in the Canadian High Arctic (Jansson & Taş, 2014), Alaskan Arctic (Ji et al, 2020), and Siberian (Belov et al, 2020) permafrost confirmed that the soil microbial diversity was highest in the active layer and decreased with depth in the permafrost layer. Compared with the active layer, the permafrost layer exhibits several unique characteristics, including low temperatures, low oxygen levels, and low water availability.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, the bacterial community diversity varied significantly between the active layer and permafrost layer. Studies in the Canadian High Arctic (Jansson & Taş, 2014), Alaskan Arctic (Ji et al, 2020), and Siberian (Belov et al, 2020) permafrost confirmed that the soil microbial diversity was highest in the active layer and decreased with depth in the permafrost layer. Compared with the active layer, the permafrost layer exhibits several unique characteristics, including low temperatures, low oxygen levels, and low water availability.…”
Section: Discussionmentioning
confidence: 92%
“…This nding further suggest gas hydrate release is an important source of methane emission from wetland soils in Qilian Mountain permafrost. During spring and summer, soil temperature increase and permafrost thawing promoted ourishly growing of wetland organisms and exponentially incresing of microbial communities [37][38][39] , which can lead to an increase in biogenic methane emision. Simultaneously, the permafrost started to thaw after the soil temperautre above 0℃ in the late spring and the thawing depth peaked in July and August.…”
Section: Discussionmentioning
confidence: 99%